Aporte turístico de los eventos realizados en la Casa de Olmedo desde el punto de vista de los participantes - Troya Santillan, Luis Patricio (2023)
The House of Olmedo is one of the most important attractions of the city of Babahoyo, thus being an axis of the tourist circuits in the province, today it has been shown that it is a potential site for different tourist recreational activities, as well as the realizations of cultural, artistic and gastronomic events thus allowing to benefit both the participants as well as the increase in tourist visits to the Casa de Olmedo. Whose main objective was to analyze the contribution of the events held in the Casa de Olmedo from the point of view of the participants, which could recognize the great impact of the events that have been carried out, allowing great advantages for the Casa de Olmedo and for entrepreneurs and artists in the province, so a calendar is proposed to hold future events in order to contribute to the tourism development of the Babahoyo canton. The techniques used in this case study were surveys and interviews also using quality measurement models, specifically the serval model to be able to recognize different positions, contrasting the information of the clients versus the entrepreneurs, thus giving rise to the advantages that entrepreneurs have after having participated in a social event or some type of gastronomic fair. As results, it was possible to recognize that the events carried out give a positive change towards the establishments of the enterprises and artists, so much so that the majority of the participants are willing to participate again since they make themselves known and thus increase the visits of clients to their stores. establishments thus allowing the creation of jobs, which is why it is important that these events take place more frequently at Casa de Olmedo.